Adrastus: Greek Law and Order - (:unkn) unknown (My University, 2016)
In Herodotaus' Histories, he relates the story of the unlucky Adrastus, who kileed his brother and then the son of the king who gave him sanctuary. A close analysis of this story reveals the underpinnings of religion and law as the ancient Greeks understood it. For this paper, I will analyze about Adrastus' first crime to Persian society, his exile, his second crime, and ultimately his punishment. To understand the material, however, one must first recognize the importance of the Blood Feud and Zeus’ laws of hospitality. I will talk about how this use to be the custom for the Greeks, and how it was the norm for the time. I will then go on to examine the second crime, against his host, and how this ultimately created an impossible situation for Croesus because he was bound by the laws of hospitality. I will then examine how and why Adrastus resolved this impasse Since Herodotus is writing about the Persians but for a Greek audience, it is then necessary to explain why Herodotus decided to write this story in The Histories. This is important, because it will lead into my analysis about how the laws have changed, and the move from the ancient laws of the blood feud and law of hospitality, which are centered on the oikos to new laws in the Solon constitution which are more appropriate to the polis. A careful analysis of the Adrastus story, therefore, allows us a rare glimpse of the ancient Greek attitude towards the changing laws as Herodotus sees it.